Implementation of Budget Absorption on Financial Performance at the Personnel and Human Resources Development Agency of Dairi Regency - Tuahman Sipayung; Rumondang Purba; Elfina Okto Posmaida Damanik (Jurnal Ilmiah Accusi, 2025)
This study aims to analyze the implementation of budget absorption and its impact on financial performance at the Civil Service and Human Resource Development Agency (BKPSDM) of Dairi Regency. Budget absorption serves as a key indicator of the effectiveness of local government program implementation. The data reveal fluctuations in budget realization from 2019 to 2021, showing an upward trend in the final quarter of each fiscal year. Employing a descriptive qualitative approach, this research uses both primary data through interviews and secondary data derived from financial reports and budget realization documents. The results show that the low level of budget absorption at the beginning of the year was influenced by unrealistic planning, delays in administrative processes, and limited human resource capacity in financial management. Conversely, in the final quarter, activities accelerated sharply, causing a workload concentration. Improvement efforts include enhancing planning systems, increasing staff competence, and optimizing digitalization in local financial processes. The findings are expected to provide valuable insights for local governments in improving the efficiency and accountability of public financial management